Tumor-derived exosomes as promising tools for cancer diagnosis and therapy - Wang, Xirui; Liu, Yanfang; Jiang, Yaowen; Li, Qinghua (Frontiers in Pharmacology, 2025)
Mounting evidences indicated that cancer cell-derived exosomes (TDEs) contribute to cancer progression and metastasis by reshaping the tumor microenvironment (TME) and interfering immunity response. TDEs contain unique biomolecular cargo, consisting of protein, nucleic acid, and lipids. In recent years, TDEs have been used as potential disease therapeutics and diagnosis biomarkers and prime candidates as delivery tools for cancer treatment. In the present review, we firstly summarized TDEs biogenesis and characteristic. Also, the role of TDEs in cancer cell metastasis and invasiveness, drug resistance, and immunosuppression was mentioned via cell-cell communication. Additionally, we concluded the current strategies for TDE-based cancer therapy, including TDEs inhibition and clearance, usage as therapeutic drug delivery vector and cancer vaccines. Furthermore, combination therapy with engineered TDEs were summarized, such as radiotherapy, photodynamic therapy, photothermal therapy, and sonodynamic therapy. Consequently, the above opens up novel and interesting opportunities for cancer diagnosis and prognosis based on TDEs, which is prospective to accelerate the clinical translation of TDEs for cancer therapy.